ChemInform Abstract: Heterogeneous Photocatalytic Nanomaterials: Prospects and Challenges in Selective Transformations of Biomass‐Derived Compounds. Issue 17 (28th April 2014) - Colmenares, Juan Carlos; Luque, Rafael
Abstract Review: 50 refs.